Best International Practices in Terms of the Award of PPP Projects and Their Comparison in Mexico, block I, 2017 - Castro Coria, Eva Grissel; Gómez Monge, Rodrigo (Unidad Editorial UPTC, 2022)
This study identifies, at a practical and normative level, if there are good international practices applied to bidding procedures, especially in the block I of the Program of Integral Strategy to Promote PPP Projects (“Programa Estrategia Integral de Impulso a los Proyectos de APP”). For this, the Concessions for infrastructure guide (Kerf et al., 1998) was used, from which the ideal steps to implement a bidding procedure were identified, the elements to be considered from each of them were extracted, the results were normalized in a scale from 0-1, and, finally, they were compared both practically and normatively. As a result, a biogram was made, which derived from the score obtained to determine the opportunity areas. The information for the practical analysis was extracted from the official website of the Program of Integral Strategy to Promote PPP Projects and the “CompraNet” platform, and for the regulatory analysis, from the Law of Public-Private Partnerships, the Law of Works and Related Services, and the Law of Procurement, Leasing and Services of the Public Sector. JEL Codes: K1, K12, C7, C79 Received: 11/11/2020.  Accepted: 21/12/2021.  Published: 01/06/2022.